Flowering and post harvest dynamics of heliconias (Heliconia spp) - Liju Abraham (Department of Pomology and Floriculture, College of Horticulture, 2013)
Floriculture has become an important business sector all over the world. In India, it has been associated with culture and heritage since very ancient times. Apart from the growing domestic demand in the last few years, export has also shown an upward trend. In the increasingly competitive international cut flower and pot plant market, new and indigenous ornamental plants play a major role. Hence it is imperative that the potential new ornamentals are evaluated so as to create further diversity in flori-businesss. Heliconias are wonderful tropical plants with multi-colour bracts, varied flower structure and long shelf life. It is the only genus in the family Heliconiaceae, which is a member of a largest taxonomical category, the order Zingiberales. Its demand for cut flower trade is increasing day-by-day because of the long vase life, attractive colour, massive appearance and exotic shape. Seven varieties of heliconia, viz., Heliconia bihai (L.) L. cv. Banana Split, H. caribaea Lamarck x H.bihai (L.) L. cv. Kawauchi, H. psittacorum L.f cv. Lady Di, H. psittacorum L.f. cv. Rubra Red, H. psittacorum L.f. x H. spathocircinata Aristeguieta cv. Golden Torch, H. psittacorum L.f. x H.spathocircinata Aristeguieta cv. Golden Torch Adrian and H. stricta Huber cv. Firebird, were evaluated for suitability for planting in landscapes and as cut flower, based on various quantitative and qualitative characters. There were significant differences in the flowering behaviour of heliconia varieties. Certain varieties were free flowering, whereas others were seasonal. Flower production was seen in all the varieties, except in Kawauchi, Golden Torch Adrian and Firebird. The varieties exhibited significant variation in all the quantitative and qualitative characters studied. Considering the bract arrangement, wax on inflorescence and fresh weight of stem, the varieties were classified as cut flowers of high performance (Golden Torch, Firebird, Lady Di, Rubra Red and Golden Torch Adrian) and low performance (Banana Split and Kawauchi). The variety Golden Torch excelled in all quantitative and qualitative characters of flowering stems, like, continuous flowering, number of spikes produced/year, fresh weight of stem less than 100 g, absence of wax and one plane arrangement of bracts. These characters have made it more ideal as cut flower and for landscape use. Firebird was promising as cut flower and landscape plant, though flowering was seasonal. Lady Di, Rubra Red and Golden Torch Adrian were ideal for the landscape, and as a cut flower for the local markets. Stage of harvest significantly influenced the vase life of heliconia flowers. At the stage when 1-2 bracts opened, the post harvest life was the best. Maximum vase life was observed in all the varieties when pre cooled at 200C for 4 hours. The flowers remained for a longer period, when pulsed with a solution containing sucrose 5 per cent + HQ 200ppm for 6 hours. Among the different holding solutions used, maximum vase life was recorded in sucrose 5 per cent + HQ 100 ppm. A storage temperature of 170C was the best for all the heliconia varieties tried, recording a life of 8.6 to 11.6 days. Packing the flowers with wet cotton plug at the peduncle end and with polythene lining was found to be the best. Based on the results obtained from the studies, a protocol for post harvest handling has been developed.